PENGARUH MORALITAS INDIVIDU DAN PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI: STUDI EKSPERIMEN PADA KONTEKS PEMERINTAHAN DAERAH - , Novita Puspasari, Dr. Eko Suwardi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This paper aims to examine the effect of individuals morality and internal control on propensity to commit fraud in governmental sector. Individuals morality and internal control are hypothesized to have interaction in influencing individuals propensity to commit fraud. Individuals who have high level of moral reasoning is hypothesized will not commit fraud in both present or absent internal control element condition. Individuals who have low level of moral reasoning is hypothesized will commit fraud in absent internal control condition. To prove those hypotheses, experiment design with 2x2 factorial design was done. There were 57 students of Magister Ekonomika Pembangunan Universitas Gadjah Mada involved in experiment. The results showed that there is an interaction between personal morality and internal control. The internal control conditions are not influencing individuals with high level of moral reasoning to commit fraud. Individuals who have low level of moral reasoning commit fraud in absent internal control condition.